The Influence of Variation in Dosage and Contact Time of Activated Carbon Adsorbent from Clove Leaf Waste on the Concentration of NH3 in Liquid Waste from Leather Industry - Pitri Lestari; Nasrul Rofiah Hidayati; Sri Wahyuningsih (Health Science UDINUS, 2023)
Hazardous due to containing organic and chemical pollutants, including NH3 waste. Adsorption method is the most effective and economical way in leather industry waste management. This study aims to determine the effectiveness of varying doses and contact times in reducing NH3 levels in leather industry waste. The activated carbon used in this study is obtained from waste clove oil distillation leaves, carbonized at 500 °C for 2 hours, and activated using 0.1 M KOH. For the adsorption process, different doses of activated carbon (0.5; 1; 1.5; 2; 2.5) grams and various contact times (5, 10, 15, 20, 25) minutes are used, with the addition of 0.3 mg/L NH3 in 50 mL solution. The adsorption results for NH3 are analyzed using UV-Vis spectrophotometer and the phenate method. The most effective NH3 reduction is achieved with a 2-gram dose, resulting in a 43.45% decrease, while the optimal contact time is 10 minutes, leading to a reduction of 68.9%. The adsorption isotherms used for activated carbon from non-activated and KOH-activated clove leaves follow the Freundlich isotherm. For non-activated carbon, the values are N = -0.5203, kf = 0.0019715, and R2 = 0.9098; for KOH-activated carbon, the values are N = -1.1885, kf = 0.0144, and R2 = 0.9858 for varying contact times